The harm of difficult to degrade plastics to animals and the surrounding environment - Gu, Sicun (Transactions on Environment, Energy and Earth Sciences, 2024)
Littering or the disposal of plastic products and particles in the environment is a current global concern. Because plastics are long-lasting and are used extensively, productivity has increased dramatically to 400 million tons per year, and only a small fraction of them is recycled or disposed of correctly. This research aimed at examining the impacts of plastic pollution on soil and marine environment especially on the changes in physical and chemical properties of the soil, the effects on plant growth and marine organisms through ingestion and entanglement. The study also notes that microplastics have negative impacts on the physical characteristics of the soil including fertility and permeability as well as the behavior of macro-organisms like earthworms, and marine life is impacted by species entanglement and ingestion of plastics leading to extensive ecological risks. Furthermore, while biodegradable plastics are more environmentally friendly, they decompose at varying speeds depending on the conditions and microorganisms. The study also highlights the importance of improved waste management, reduction in the use of plastics, enhancement of recycling and biodegradation studies to minimize the adverse effects on the environment in the long run. This work assists in increasing the public’s understanding of the global problem of plastic pollution and promotes the need for a universal approach to minimizing the negative impact on the environment.